Exploring backpackers' perceptions of the hostel service quality - Brochado, A. (2016)
Purpose – The aim of this paper is to contribute to the understanding of backpackers’s evaluation of service quality provided by hostels by developing a battery of items to assess perceptions of the overall hostel experience. Design/methodology/approach – Scale development took a mixed approach that combines qualitative and quantitative research. First, the authors performed a content analysis of reviews provided by guests in hostel booking web sites, in-depth interviews with hostel managers and focus groups with guests, to develop a battery of items to assess the hostel experience from the guests’ perspective. Then, a quantitative survey (n = 222) was conducted, to explore the dimensionality of service quality in this sector. Lisbon hostels are the target of this study, as they received several awards based on the online reviews of backpackers. Findings – The results revealed that service quality is a multidimensional concept and includes six dimensions, namely, social atmosphere, location and city connection, staff, cleanliness, security and facilities. Regression results revealed that the social atmosphere appears to be a core service dimension crucial to create a sense of hostel guest’s overall quality. Originality/value – The findings suggest that service quality scales should incorporate the specific characteristics of the hotel industry. The quality of the staff and the social atmosphere are of utmost importance to enhance the hostel backpacker experience.